Memahami Metode Pendidikan Akhlak dalam Perspektif Islam: Perbandingan Pemikiran Imam Al-Ghazali dan Abdullah Nashih ‘Ulwan - Putri, Febrianti Rosiana; Mukhlas, Abdulloh Arif (Al-Jadwa: Jurnal Studi Islam, 2023)
In an Islamic perspective, morals have an important role in living life. The morals possessed by a child are a form of habit seen from their immediate environment, namely the family. Moral education for children requires good methods, in order to facilitate educators in educating and forming good children's morals. Imam Al-Ghazali and Abdullah Nashih 'Ulwan are some of the Islamic figures who contributed ideas regarding methods of moral education. This study writes about how the method of moral education in children in the perspective of Imam Al-Ghazali and the perspective of Abdullah Nashih 'Ulwan and how is the method of moral education in children compared in the perspective of both? By using a comparative descriptive method, this literature research concludes that there are similarities in the thoughts of Imam Al-Ghazali and Abdullah Nashih 'Ulwan regarding methods of moral education, namely methods of exemplary, habituation, advice, punishment and rewards. Apart from having points of similarity, the two figures also have different points of view regarding the method of moral education in its application and in its concept.